2019
DOI: 10.1007/s10971-019-04933-4
|View full text |Cite
|
Sign up to set email alerts
|

Silica-silk fibroin hybrid (bio)aerogels: two-step versus one-step hybridization

Abstract: In this study, silk fibroin as a highly promising naturally occurring biopolymer extracted from silkworm cocoon is applied to mechanically reinforce silica aerogels. To this aim, two different approaches for the incorporation of silk fibroin into the silica network are compared: (1) a one-step acid catalyzed and (2) a two-step acid-base catalyzed sol-gel reaction. The total organosilane concentration, as well as the SF to silane mass fractions, regulated the hybridization process to proceed either through a on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
(22 reference statements)
0
20
1
Order By: Relevance
“…The stress−strain curves in Figure 5i−k display the typical deformation behavior of highly porous 3D scaffolds, i.e., linear elastic behavior at low strain followed by a successive pore collapse-related stress reduction at intermediate strains, and finally, a plastic yielding plateau with subsequent strain hardening at higher strain. We obtained a Young's modulus of ε = 283.5 kPa (for Silica-3-SF-CM-RGD-60) and ε = 31.98 kPa (for Silica-0.6-SF-CM-RGD-60) along the pore (freezing) direction (Figure 5i), which is significantly higher than the values for previously reported pristine silk fibroin (0.09 MPa) 27,28 and silica aerogels (5−20 kPa). 29 3.4.…”
Section: Resultscontrasting
confidence: 52%
“…The stress−strain curves in Figure 5i−k display the typical deformation behavior of highly porous 3D scaffolds, i.e., linear elastic behavior at low strain followed by a successive pore collapse-related stress reduction at intermediate strains, and finally, a plastic yielding plateau with subsequent strain hardening at higher strain. We obtained a Young's modulus of ε = 283.5 kPa (for Silica-3-SF-CM-RGD-60) and ε = 31.98 kPa (for Silica-0.6-SF-CM-RGD-60) along the pore (freezing) direction (Figure 5i), which is significantly higher than the values for previously reported pristine silk fibroin (0.09 MPa) 27,28 and silica aerogels (5−20 kPa). 29 3.4.…”
Section: Resultscontrasting
confidence: 52%
“…We used different mass fractions to identify an optimum ratio to achieve a balance of the The lowest bulk density was obtained for the sample X-SF-MXene5-GO (0.006 g cm −3 ), which is considerably lower than that of the previously developed SF-based aerogel composite of ∼0.1 g cm −3 . 14 The SEM images in Figure 2a−c demonstrate the long-range and hierarchically aligned nacre-mimetic brick-and-mortar or lamella-bridge network structures. In such nacre-mimetic structures, GO and MXene 2D nanosheet building blocks were well-dispersed and intertwined together with the crosslinked SF biopolymer and constituted the bridge structures (Figure 2d−f).…”
Section: Resultsmentioning
confidence: 99%
“…9,10 In this regard, lightweight foams based on sustainable precursors with cellular microarchitecture have demonstrated enormous potential for processing advanced structural and functional materials. 11 Our previous studies have shown the potential of novel silk fibroin (SF)-based aerogels, denoted AeroSF, 12 and their composite counterparts 13,14 for diverse advanced applications, such as thermal insulation, water/oil separation, and as scaffolds for bone repair. 15,16 SF, a biopolymer extracted from Bombyx mori silkworm cocoon, is a biocompatible and biodegradable fibrous protein.…”
Section: Introductionmentioning
confidence: 99%
“…However, the formation of later bonds has been thoroughly investigated in our previous works for the composite of silica and SF through in situ sol-gel reaction and self-assembly process. [4,7,[26][27][28] A major part of gel printing is devoted to controlling the gel viscosity and optimizing its rheological performance to obtain the best printability window for the as-synthesized gels. In extrusionbased 3D printing, printability is generally defined as the "suitable" extrudability, struts' formation, and shape fidelity which all indicate the degree of dimensional preciseness of the printed ob-ject in comparison to the computer-aided design model one.…”
Section: Resultsmentioning
confidence: 99%